Integrated Stress Response Couples Mitochondrial Protein Translation With Oxidative Stress Control. Issue 18 (2nd November 2021) - Zhang, Guangyu; Wang, Xiaoding; Li, Chao; Li, Qinfeng; An, Yu A.; Luo, Xiang; Deng, Yingfeng; Gillette, Thomas G.; Scherer, Philipp E.; Wang, Zhao V.
Abstract : Background: The integrated stress response (ISR) is an evolutionarily conserved process to cope with intracellular and extracellular disturbances. Myocardial infarction is a leading cause of death worldwide. Coronary artery reperfusion, the most effective means to mitigate cardiac damage of myocardial infarction, causes additional reperfusion injury. This study aimed to investigate the role of the ISR in myocardial ischemia/reperfusion (I/R). Methods: Cardiac-specific gain- and loss-of-function approaches for the ISR were used in vivo. Myocardial I/R was achieved by ligation of the cardiac left anterior descending artery for 45 minutes followed by reperfusion for different times. Cardiac function was assessed by echocardiography. Cultured H9c2 cells, primary rat cardiomyocytes, and mouse embryonic fibroblasts were used to dissect underlying molecular mechanisms. Tandem mass tag labeling and mass spectrometry was conducted to identify protein targets of the ISR. Pharmacologic means were tested to manipulate the ISR for therapeutic exploration. Results: We show that the PERK (PKR-like endoplasmic reticulum resident kinase)/eIF2α (α subunit of eukaryotic initiation factor 2) axis of the ISR is strongly induced by I/R in cardiomyocytes in vitro and in vivo. We further reveal a physiologic role of PERK/eIF2α signaling by showing that acute activation of PERK in the heart confers robust cardioprotection against reperfusion injury. In contrast, cardiac-specific deletion of PERK aggravates cardiac responses to reperfusion. Mechanistically, the ISR directly targets mitochondrial complexes through translational suppression. We identify NDUFAF2 (NADH:ubiquinone oxidoreductase complex assembly factor 2), an assembly factor of mitochondrial complex I, as a selective target of PERK. Overexpression of PERK suppresses the protein expression of NDUFAF2 and PERK inhibition causes an increase of NDUFAF2. Silencing of NDUFAF2 significantly rescues cardiac cell survival from PERK knockdown under I/R. We show that activation of PERK/eIF2α signaling reduces mitochondrial complex–derived reactive oxygen species and improves cardiac cell survival in response to I/R. Moreover, pharmacologic stimulation of the ISR protects the heart against reperfusion damage, even after the restoration of occluded coronary artery, highlighting clinical relevance for myocardial infarction treatment. Conclusions: These results suggest that the ISR improves cell survival and mitigates reperfusion damage by selectively suppressing mitochondrial protein synthesis and reducing oxidative stress in the heart. Abstract : Supplemental Digital Content is available in the text.